Driven Back to Eden - Roe, Edward Payson, 1838-1888 (Salt Lake City, UT : Project Gutenberg, 2004)
"Driven Back to Eden" by Edward Payson Roe is a novel written during the late 19th century. The story appears to focus on the life of a struggling city family that decides to abandon their cramped urban existence in search of a healthier and more fulfilling life in the countryside. Central to the narrative is Robert Durham, a father who grapples with the challenges of raising his children in a crowded city, and his wife, Winifred, as they both navigate the complexities of household management and family well-being. The opening of the novel introduces readers to the Durham family dynamics, highlighting Robert's concerns about the influences of city life on his children, particularly in contrast with their fragile health and the distractions of urban society. As the chapter progresses, Robert's reflections lead him to the compelling decision to move his family to the country to cultivate a better life. The stage is set for their subsequent journey and the challenges they will face adjusting to their new environment. The narrative captures the warmth of familial bonds while presenting relatable issues of parenthood, responsibility, and the desire for a simpler, healthier life. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Charles Franks and the Online Distributed Proofreading Team
Keywords: Country life -- Juvenile fiction; Farm life -- Juvenile fiction; New York (State) -- Juvenile fiction; Families -- Juvenile fiction